2022
DOI: 10.1002/leap.1472
|View full text |Cite
|
Sign up to set email alerts
|

Use of preprint peer review to educate and enculturate science undergraduates

Abstract: Key points Undergraduate science education should include education in scholarly practices like peer review. Authentic experiences in peer review increase science literacy and science identity. Peer review of preprints provides a means for undergraduates to be involved in peer review that is independent of journal gatekeeping processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
4
8
0
Order By: Relevance
“…We observe that open chromatin in blood (E116, GM12878 Lymphoblastoid Cells; E124, Monocytes-CD14+ RO01746 Primary Cells; E041, Primary T helper cells PMA-I stimulated) and rectum (E102, Rectal Mucosa Donor 31) is positively associated with SNP-disease association in both diseases; this is consistent with a previous study where blood cell types are found to be relevant in many autoimmune diseases, including UC and CD [33]. In addition, symptoms or complications in rectum is also observed in UC and CD [34]. Interestingly, open chromatin in GI-intestine (E085, fetal intestine small) is negatively associated with SNP-disease association, along with ohter intestine tissues (E084, fetal intestine large and E109, small intestine, with the 61th and 86th smallest tissue weight, respectively, amongst 127 contexts).…”
Section: Resultssupporting
confidence: 89%
“…We observe that open chromatin in blood (E116, GM12878 Lymphoblastoid Cells; E124, Monocytes-CD14+ RO01746 Primary Cells; E041, Primary T helper cells PMA-I stimulated) and rectum (E102, Rectal Mucosa Donor 31) is positively associated with SNP-disease association in both diseases; this is consistent with a previous study where blood cell types are found to be relevant in many autoimmune diseases, including UC and CD [33]. In addition, symptoms or complications in rectum is also observed in UC and CD [34]. Interestingly, open chromatin in GI-intestine (E085, fetal intestine small) is negatively associated with SNP-disease association, along with ohter intestine tissues (E084, fetal intestine large and E109, small intestine, with the 61th and 86th smallest tissue weight, respectively, amongst 127 contexts).…”
Section: Resultssupporting
confidence: 89%
“…This knowledge has demystified for these students a critical component of success in STEM fields, that of contributing to scientific knowledge through publication. In line with our overarching goal, the broader data in the literature suggests that such efforts lead to increased development of scholarly identity and, therefore, better STEM engagement and retention, particularly for underrepresented and minoritized students (Burt et al, 2023; Hernandez et al, 2017; McDowell et al, 2022; Perez et al, 2014).…”
Section: Discussionsupporting
confidence: 61%
“…There are practices that engage students in authentic authorship experiences with publishable products (Burks & Chumchal, 2009; Giuliano et al, 2019; Guilford, 2001), though none have been described in the field of synthetic biology. Fewer tools exist to measure learning gains with respect to writing, or that teach the more abstract processes of peer review and scientific publishing (McDowell et al, 2019), and more development is needed in these areas(McDowell et al, 2022). Demystifying authorship and publication processes was shown to improve student learning outcomes and foster a greater sense of scientific identity among graduate students (Sletto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, peer review represents part of science, technology, engineering, and math (STEM) education’s “hidden curriculum” of unstated norms, values, skills, and expectations that are untaught yet required for success ( 14 ). Since peer review is integral to the scientific process and central to the identity of a scientist, we envision a paradigm shift that makes teaching peer review integral to undergraduate science education ( 15 ). Just as early research experiences help students form a scientific identity ( 16 ) and develop scientific literacy ( 17 ), so too can early scholarship experiences in peer review.…”
Section: Introductionmentioning
confidence: 99%